The Islamization of the Malay worldview: a cultural transformation - Mamat, Ismail (IIUM Press, 2011)
The Malay history has been well-documented and much has been written about it by many authors either by the Malays or by the non-Malays as well as the Orientalists. They wrote on various genres of literature, culture and other aspects of the Malays. Some of their findings and conclusions are acceptable. But for some others, because of their adoption of various Western social theories, their application to the study of the Malay society yield untenable results. Syed MuÍammad Naquib al-Attas in his influential works such as the Preliminary Statement on a General Theory of the Islamization of the Malay-Indonesian Archipelago, has argued that some of the theories and elaborations particularly by the Orientalists pertaining to Islam and the Islamization of the Malay Archipelago cannot be considered as having achieved the scientific rank of theory, or even in some cases that of hypothesis. As argued by him, the coming of Islam was the most momentous event for the Malays. It constitutes a new period in their history. The process of Islamization generally refers to the process that brought about the phenomenon of historical and cultural impact of Islam upon the Malay world which revolutionized its vision of reality and existence into distinctive Islamic worldview.